A grande fraude - Baldraia, Fernando (Afro-Ásia, 2020)
Resenha de: Graham, Jessica Lynn. Shifting the Meaning of Democracy: Race, Politics, and Culture in the United States and Brazil. Los Angeles: University of California Press, 2019. 365p.